If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15(-4g + 8) + 6 = -1 + -1(9 + -8g) Reorder the terms: 15(8 + -4g) + 6 = -1 + -1(9 + -8g) (8 * 15 + -4g * 15) + 6 = -1 + -1(9 + -8g) (120 + -60g) + 6 = -1 + -1(9 + -8g) Reorder the terms: 120 + 6 + -60g = -1 + -1(9 + -8g) Combine like terms: 120 + 6 = 126 126 + -60g = -1 + -1(9 + -8g) 126 + -60g = -1 + (9 * -1 + -8g * -1) 126 + -60g = -1 + (-9 + 8g) Combine like terms: -1 + -9 = -10 126 + -60g = -10 + 8g Solving 126 + -60g = -10 + 8g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-8g' to each side of the equation. 126 + -60g + -8g = -10 + 8g + -8g Combine like terms: -60g + -8g = -68g 126 + -68g = -10 + 8g + -8g Combine like terms: 8g + -8g = 0 126 + -68g = -10 + 0 126 + -68g = -10 Add '-126' to each side of the equation. 126 + -126 + -68g = -10 + -126 Combine like terms: 126 + -126 = 0 0 + -68g = -10 + -126 -68g = -10 + -126 Combine like terms: -10 + -126 = -136 -68g = -136 Divide each side by '-68'. g = 2 Simplifying g = 2
| 5p+14=8p(-2) | | 60n^2+258n+168=0 | | 2X^3-3X^2-3=0 | | 5.3x-3.24=3.18-5.4x | | 5p+14=8p-(-2) | | -3x+3=-33 | | 2.1x-5.25=3.15-3.5x | | 9x+7=6x+8 | | 2.1x-5.25=3.15-3.5 | | -7x-12+20x=14-12x+25x-10 | | 5x^2+46x-40=0 | | 3n+7=5n+3 | | 9x+5y=11x-8y | | 3x-5+1=-2x+7 | | 7+9(x-3)=1-6(x-9) | | 9y+5x=11y-8x | | 6y+5=11y+30 | | (-12a)(ab)=0 | | 18x^2-72x+40=0 | | (-12abc)(4ab)=0 | | 2(x-5)=-10+2x | | 150=4x-160 | | 5*0+4y=0 | | 0=4x^2-14x+3 | | 2+5(x-8)=11-7(x-7) | | 3n+4=3n+5 | | 6x+8=10x-40 | | 2x^2+12x=-110 | | (3x-7m)(5x+3m)= | | 7+(-2)+5= | | 3a+4=3a-8 | | 2a+3b-2a-b= |